Effect of automated fiber placement (AFP) manufacturing signature on mechanical performance of composite structures. (15th November 2019) - Nguyen, Minh Hoang; Vijayachandran, Avinkrishnan A.; Davidson, Paul; Call, Damon; Lee, Dongyeon; Waas, Anthony M.
Abstract: A comprehensive and detailed experimental study of the influence of imperfections caused during Automated Fiber Placement (AFP) manufacturing is reported. Specimens with controlled gap and overlap imperfections of varying sizes and distribution were manufactured and tested. Pre-test microscopy inspection has been conducted to quantify the change in geometry due to compaction. Test results show significant knockdown in stiffness and strength due to gaps, specifically with larger gap sizes showing higher knockdown. Overlaps, on the other hand, may provide improvement in tensile properties and show negligible change in compressive properties. Digital image correction (DIC), in situ inspection with edge cameras and post-test microscopy analyses provide a detailed insight into the failure progression and modes.